Organic Amendments Enhance the Remediation Potential of Economically Important Crops in Weakly Alkaline Heavy Metal-Contaminated Bauxite Residues - Xingfeng Zhang; Qiankui Yu; Bo Gao; Maosheng Hu; Hongxu Chen; Yexi Liang; Haifeng Yi (Agriculture)
Heavy metal (HM) pollution in soil has emerged as a global concern. This study introduces a novel approach to ameliorate HM-contaminated bauxite residues (BRs) characterized by weak alkalinity and low nutrient levels. By cultivating economically important crops, this method aims to enhance the remediation of heavy metal-contaminated BR while simultaneously promoting economically important crop production. Using a pot experiment, we investigated the effects of four organic amendments (peat, cow dung, bagasse, and microbial fertilizer) on the growth and BR properties of four economically important crops (castor, ramie, sugarcane, and cassava). The application of these organic amendments obviously reduced the BRs pH by 0.6–2.22%. Organic amendment applications significantly increased the soil organic matter (SOM) content and cation exchange capacity (CEC) by 14.35 to 179.94% and 6.87 to 12.14%, respectively. Additionally, the use of organic amendments enhanced BR enzyme activity, with microbial fertilizer demonstrating a substantial increase in BR invertase activity from 131.49 to 687.61%. Superoxide dismutase (SOD) activity and malondialdehyde (MDA) content remarkably increased, whereas catalase (CAT) activity did not show significant differences. HM content analysis in different plant parts revealed HMs primarily found in the plant roots. Organic amendments mitigate the transfer of HMs from roots to shoots, thereby reducing HM content in the available parts of economically important crops. The pot experiment results demonstrated the effectiveness of the four combinations in achieving both the repair and production objectives. These combinations include planting castor and ramie with cow dung, sugarcane with peat, and cassava with bagasse. These findings underscore the feasibility of cultivating economically important crops in HM-contaminated BRs, enhancing BR quality, and augmenting farmers’ incomes. This study provides a scientific basis for mine remediation and reclamation using BRs.